Polk County farmland preservation survey - Janke, James; Trechter, David (My University, 2012)
The purpose of this study was to gather opinions from agricultural stakeholders with respect to farmland preservation and agricultural issues in Polk County.
39 p.
Keywords: Polk County (Wis.); Agriculture--Wisconsin; Polk County (Wis.)--Survey; Public opinion--Wisconsin--Polk County